PERSPEKTIF NILAI DALAM KONSELING : MEMBANGUN INTERAKSI EFEKTIF ANTARA KONSELOR - KLIEN - Sigit Sanyata (Paradigma, 2006)
A professional counselor is a figure that can perform as an example for the clients and society. The behaviors based on ethical principles are not limited to the counseling process but apply to all situations requiring them. Ethical issues become bases for counselors to always take account of morality, ethics, rules of law, professionalism, and service with empathy. In a counseling service, the counselor’s position brings about logical consequences requiring personal wisdom to understand the client’s belief and value system. In practice, a counselor often find a belief and value system different from, or even contrary to, his or her own. Such a situation makes a counselor face a dilemma whether he or she will accept the client’s belief and value system or interfere with the client’s. Some factors that can make a counselor behave appropriately in relation to the value perspective are that: 1) the counselor has a positive personal quality, 2) he or she is capable ofunderstanding ethical issues in counseling, 3) he or she has a cultural awareness in the multi-cultural context, 4) he or she can build an effective counselor-client relationship, and 5) he or she can understand the client’s belief principles and value system.Keywords: value system, belief, counseling